Associations, new records, and a new species of Atopsyche from northwestern Argentina and southern Bolivia (Trichoptera: Hydrobiosidae) - Martin, Paola A.r. (Zootaxa, 2006)
The larva, pupa, and the adult male of a new species of Atopsyche (Trichoptera: Hydrobiosidae) from northwestern Argentina and southern Bolivia are described and illustrated. Atopsyche (Atopsaura) yunguensis new species, is close to A. (Atopsaura) lobosa Ross and King 1952 and A.(Atopsaura) spinosa Navás 1930. In the new species the parapods are large, broadened at the tip, and dorsally curved toward the midline, the apical segment of the inferior appendages is curved toward the midline, and the phallotheca bears a dorsal bilobed lobe with lateral spines. Preimaginal stages of A. spinosa and A. callosa are described and illustrated and represent new records from Bolivia. In addition, A. (Atopsyche) kamesa is newly recorded from Argentina.